New Threats to Freedom. - Bellow, Adam (Templeton Press, 2012)
New Threats to FreedomIn the twentieth century, free people faced a number of mortal threats, ranging from despotism, fascism, and communism to the looming menace of global terrorism. While the struggle against some of these overt dangers continues, some insidious new threats seem to have slipped past our intellectual defenses. These often unchallenged threats are quietly eroding our hard-won freedoms and, in some cases, are widely accepted as beneficial. In New Threats to Freedom, editor and author Adam Bellow has assembled an all-star lineup of innovative thinkers to challenge these insidious n.